Bipolar Disorder Management Physician Oder: New Initiatives at the Mental Hospital of Ministry of Health in Saudi Arabia - Alomi, Yousef Ahmed; Alsolami, Nora; Alqahtani, Nada; Alsairi, Abeer; Aldossari, Ban (Journal of Pharmacy Practice and Community Medicine)
The national psychiatric pharmacy program is new system founded in the Kingdom of Saudi Arabia. The program of mental health care services at Ministry of health. The new program started with several initiatives projects including evidence named medicine guidelines. The new project of bipolar disorder management physician order was one the outcome of the program. The guidelines development through task force committee by Pharmacy department at the most prominent mental hospital, in Riyadh region in Saudi Arabia. The project prevents antipsychotic-related problems and avoids the unnecessary economic burden on the healthcare system. The new initiative’s project is new in Saudi Arabia, Gulf and Middle East counties.
Keywords: Bipolar Disorder; Management; Physician Oder; Ministry of Health; Saudi Arabia